STUDENT’S PERCEPTIONS OF ENGLISH CLASSROOM ASSESSMENT DURING COVID-19 PANDEMIC - Yulia Dian Nafisah; Anton Haryadi; Junaidi Mistar (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2021)
This research aims at investigating the student perceptions of English classroom assessment at an Islamic Senior High School during Covid-19 pandemic. The research involved 314 students from 20 different classes across three academic years. The instrument used was 30 five-point Likert scale items from Students’ Perceptions of Assessment Questionnaire (SPAQ) developed by Waldrip, Fisher, & Dorman (2008). After the data were collected and analyzed for reliability and validity using SPSS20, it was found that the internal consistency/reliability was 0.75. The internal consistency score was high, which means that the average inter-item correlation was high. The discriminant validity was also high, which implies that the instrument was valid. The data were then analyzed descriptively and reported in mean and standard deviation format.  It was found that the highest mean belonged to diversity scale and the lowest belonged to student consultation. It means that although the mean of each scale was high, it is expected that the students is consulted and authenticity is improved in this school.